2020
DOI: 10.1016/j.cub.2020.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of the Emblematic White Cheese-Making Fungus Penicillium camemberti and Its Diversification into Two Varieties

Abstract: Highlights d The molds used in soft cheeses result from multiple domestication steps d The clonal and fluffy Penicillium camemberti displays strong signs of domestication d Two varieties occur in P. camemberti, with contrasted phenotypic features

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
143
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(163 citation statements)
references
References 71 publications
17
143
2
1
Order By: Relevance
“…The remaining fungi from Table 4 (Cladosporium xylophilum, C. macrocarpum, Penicillium fuscoglaucum, Mucor racemosus, Stagonosporopsis lupini) were commonly isolated from plants and foods [45][46][47][48][49], and Botryotrichum domesticum from a house [50]. As far as we know, no reports on their presence on wall paintings have been published, other than for C. macrocarpum [41,51].…”
Section: Ecology Of Fungal Isolatesmentioning
confidence: 99%
“…The remaining fungi from Table 4 (Cladosporium xylophilum, C. macrocarpum, Penicillium fuscoglaucum, Mucor racemosus, Stagonosporopsis lupini) were commonly isolated from plants and foods [45][46][47][48][49], and Botryotrichum domesticum from a house [50]. As far as we know, no reports on their presence on wall paintings have been published, other than for C. macrocarpum [41,51].…”
Section: Ecology Of Fungal Isolatesmentioning
confidence: 99%
“…biforme was also isolated from traditional artisan Italian cave cheese by Anelli et al [ 52 ]. Moreover, a recent study carried out by Ropars et al [ 53 ] suggests that wild strains identified in the literature as P . commune correspond to either P .…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of fungi and bacteria was not well understood scientifically until the nineteenth century (Barnett 2003), some human cultures were able to control fermentation sufficiently to favor the evolution of domesticated strains of particular fermentation species. Such is the case for some Penicillium fungi associated with cheese (Ropars et al 2020), for example, Saccharomyces cerevisiae associated with bread, beer, and wine and Aspergillus oryzae associated with sake, miso, and shoyu (soy sauce; Watarai et al 2019). The descendants of some such domesticates, including S. cerevisiae and A. oryzae, have subsequently been subject to further domestication associated with the industrialization of fermentation (Sicard and Legras 2011;Watarai et al 2019).…”
Section: S000mentioning
confidence: 99%